Mapping dry-season tree transpiration of an oak woodland at the catchment scale, using object-attributes derived from satellite imagery and sap flow measurements - Reyes-Acosta, J Leonardo; Lubczynski, Maciek W (Agricultural and Forest Meteorology, 2013)
Abstract Tree transpiration is an important plant-physiological process that influences the water cycle, thereby influencing ecosystems and even the quantity of available water resources. However, direct tree-transpiration measurements, particularly at large spatial scales, are still rare, due to the complexities associated with natural ecosystems. In this study we describe a scaling-up method for quantifying dry-season tree transpiration (Tc) of the Sardón catchment, located in Central-Western Spain, 50 km west of Salamanca. The method is applied to an oak woodland in that catchment which is dominated by two tree species: evergreen Quercus ilex and deciduous Quercus pyrenaica (Q.i. and Q.p., respectively). The method comprises five complementary steps: (a) sap-flux density (Jp) measurement; (b) definition of biometric-upscaling functions; (c) spatial scaling-up of tree transpiration using high-resolution remote-sensing-derived object attributes (50–60 cm per pixel); (d) modelling of dry-season temporal sap-flow variability; and (e) an assessment of the robustness/uncertainty of the method. The proposed method was applied to assess dry-season tree transpiration, however if there is appropriate sap flow data available, it can also be applied during any season of the year. The application of the proposed method to map tree transpiration in the Sardón catchment resulted in a mean Jp = 58.4 cm3 cm−2 day−1 for Q.p., characterized by tree density of 19 trees ha−1, and a mean Jp = 37.1 cm3 cm−2 day−1 for Q.i., characterized by tree density of 4 trees ha−1. The Jp data varied as dependent on the weather conditions and not on the change of soil moisture. The mean normalised tree transpiration (Tt) estimated per species, was also higher for Q.p. (1.19 mm day−1 ±8%) than for Q.i. (0.83 mm day−1 ±25%) trees. The remote-sensing scaling up of tree transpiration for the Sardón catchment resulted in a low mean dry-season Tc = 0.045 mm day−1 (±1%) typical for water limited environments with sparse tree coverage (average ≈7%). In that Tc, Q.p. represented 79%, whereas Q.i. 21%. The dry-season Tc varied spatially at 1 ha resolution but barely temporally throughout the dry season. The obtained Tc maps can be readily used as input for distributed models in water resources and land management decision-making.
Keywords: HFD; Quercus ilex; Quercus pyrenaica; Sap-flow scaling-up; Semi-arid open-forest; Transpiration

Long-term transpiration change with rainfall decline in a Mediterranean Quercus ilex forest - LIMOUSIN, J. M.; Rambal, S.; OURCIVAL, J. M.; Rocheteau, A.; JOFFRE, R.; RODRIGUEZ-CORTINA, R. (Global Change Biology, 2009)
In the Mediterranean basin, precipitation is expected to decline as a consequence of climate change. The response of a Quercus ilex forest in southern France to such a decline in water availability was studied using a 4-year throughfall exclusion experiment. Seasonal courses of sap flow and leaf water potential were obtained from 2004 to 2007 and used to characterize tree water relations in a control and a dry treatment. The experiment reduced the average precipitation input to the soil by 29%, and resulted in a 23% reduction in annual transpiration. Soil water potential was significantly lower in the dry treatment only during summer drought, but transpiration was reduced all year round even during well-watered periods. Despite a tight stomatal control over transpiration, whole-tree hydraulic conductance was found to be lower in the trees growing in the driest conditions. This reduction in water transport capacity was observed jointly with a reduction in leaf transpiring area. Canopy leaf area decreased by 18% in the dry treatment as a consequence of the throughfall exclusion, which was found to validate the ecohydrological equilibrium theory.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought; ecohydrology; Hydraulic conductance; leaf area index; leaf water potential; Mediterranean evergreen forest; Quercus ilex; throughfall exclusion; Transpiration

What limits evaporation from Mediterranean oak woodlands – The supply of moisture in the soil, physiological control by plants or the demand by the atmosphere? - Baldocchi, Dennis D.; Xu, Liukang (Advances in Water Resources, 2007)
The prediction of evaporation from Mediterranean woodland ecosystems is complicated by an array of climate, soil and plant factors. To provide a mechanistic and process-oriented understanding, we evaluate theoretical and experimental information on water loss of Mediterranean oaks at three scales, the leaf, tree and woodland. We use this knowledge to address: what limits evaporation from Mediterranean oak woodlands – the supply of moisture in the soil, physiological control by plants or the demand by the atmosphere? The Mediterranean climate is highly seasonal with wet winters and hot, dry summers. Consequently, available sunlight is in surplus, causing potential evaporation to far exceed available rainfall on an annual basis. Because the amount of precipitation to support woody plants is marginal, Mediterranean oaks must meet their limited water supply by a variety of means. They do so by: (1) constraining the leaf area index of the landscape by establishing a canopy with widely spaced trees; (2) reducing the size of individual leaves; (3) by adopting physiological characteristics that meter the use of water (e.g. regulating stomatal, leaf nitrogen/photosynthetic capacity and/or hydraulic conductance); (4), by tapping deep supplies of water in the soil; (5) and/or by adopting a deciduous life form, which reduces the time interval that the vegetation transpires.
Keywords: ecohydrology; evaporation; quercus douglasii; savanna; Transpiration

Estimation of Mediterranean forest transpiration and photosynthesis through the use of an ecosystem simulation model driven by remotely sensed data - Anselmi, Silvia; Chiesi, Marta; Giannini, Monica; Manes, Fausto; Maselli, Fabio (Global Ecology and Biogeography, 2004)
Aim This paper investigates the use of an ecosystem simulation model, FOREST-BGC, to estimate the main ecophysiological processes (transpiration and photosynthesis) of Mediterranean coastal forest areas using remotely sensed data. Location Model testing was carried out at two protected forest sites in central Italy, one of which was covered by Turkey oak (Circeo National Park) and the other by holm-oak (Castelporziano Estate). Methods At both sites, transpiration and photosynthesis measurements were collected in the field during the growing seasons over a four-year period (1999 and 2001 for the Turkey oak; 1997, 1999 and 2000 for the holm-oak). Calibration of the model was obtained through combining information derived from ground measurements and remotely sensed data. In particular, remote sensing estimates of the Leaf Area Index derived from 1 × 1-km NOAA AVHRR Normalized Difference Vegetation Index data were used to improve the adaptation of the model to local forest conditions. Results The results indicated different strategies regarding water use efficiency, ‘water spending’ for Turkey oak and ‘water saving’ for holm-oak. The water use efficiency for the holm-oak was consistently higher than that for the Turkey oak and the relationship between VPD and WUE for the holm-oak showed a higher coefficient of determination (R2 = 0.9238). Comparisons made between the field measurements of transpiration and photosynthesis and the model estimates showed that the integration procedure used for the deciduous oak forest was effective, but that there is a need for further studies regarding the sclerophyllous evergreen forest. In particular, for Turkey oak the simulations of transpiration yielded very good results, with errors lower than 0.3 mm H2O/day, while the simulation accuracy for photosynthesis was lower. In the case of holm-oak, transpiration was markedly overestimated for all days considered, while the simulations of photosynthesis were very accurate. Main conclusions Overall, the approach offers interesting operational possibilities for the monitoring of Mediterranean forest ecosystems, particularly in view of the availability of new satellite sensors with a higher spatial and temporal resolution, which have been launched in recent years.
Keywords: AVHRR; Ecosystem; FOREST-BGC; Mediterranean area; Modelling; photosynthesis; Quercus cerris; Quercus ilex; Transpiration; water efficiency

Estimation of Mediterranean forest transpiration and photosynthesis through the use of an ecosystem simulation model driven by remotely sensed data - Anselmi, Silvia; Chiesi, Marta; Giannini, Monica; Manes, Fausto; Maselli, Fabio (Global Ecology and Biogeography, 2004)
Aim This paper investigates the use of an ecosystem simulation model, FOREST-BGC, to estimate the main ecophysiological processes (transpiration and photosynthesis) of Mediterranean coastal forest areas using remotely sensed data. Location Model testing was carried out at two protected forest sites in central Italy, one of which was covered by Turkey oak (Circeo National Park) and the other by holm-oak (Castelporziano Estate). Methods At both sites, transpiration and photosynthesis measurements were collected in the field during the growing seasons over a four-year period (1999 and 2001 for the Turkey oak; 1997, 1999 and 2000 for the holm-oak). Calibration of the model was obtained through combining information derived from ground measurements and remotely sensed data. In particular, remote sensing estimates of the Leaf Area Index derived from 1 × 1-km NOAA AVHRR Normalized Difference Vegetation Index data were used to improve the adaptation of the model to local forest conditions. Results The results indicated different strategies regarding water use efficiency, ‘water spending’ for Turkey oak and ‘water saving’ for holm-oak. The water use efficiency for the holm-oak was consistently higher than that for the Turkey oak and the relationship between VPD and WUE for the holm-oak showed a higher coefficient of determination (R2 = 0.9238). Comparisons made between the field measurements of transpiration and photosynthesis and the model estimates showed that the integration procedure used for the deciduous oak forest was effective, but that there is a need for further studies regarding the sclerophyllous evergreen forest. In particular, for Turkey oak the simulations of transpiration yielded very good results, with errors lower than 0.3 mm H2O/day, while the simulation accuracy for photosynthesis was lower. In the case of holm-oak, transpiration was markedly overestimated for all days considered, while the simulations of photosynthesis were very accurate. Main conclusions Overall, the approach offers interesting operational possibilities for the monitoring of Mediterranean forest ecosystems, particularly in view of the availability of new satellite sensors with a higher spatial and temporal resolution, which have been launched in recent years.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: AVHRR; Ecosystem; FOREST-BGC; Mediterranean area; Modelling; photosynthesis; Quercus cerris; Quercus ilex; Transpiration; water efficiency

Non-steady-state modelling of water transfer in a Mediterranean evergreen canopy - Lhomme, J. P.; Rocheteau, A.; OURCIVAL, J. M.; Rambal, S. (Agricultural and Forest Meteorology, 2001)
A model simulating the diurnal pattern of water transfer within a Holm oak (Quercus ilex) canopy in Mediterranean conditions has been designed. It combines a non-steady-state hydraulic model with a transpiration model. The hydraulic model includes a reservoir represented by a capacitance, a soil–plant hydraulic resistance and a storage hydraulic resistance connected to the capacitance. It simulates the diurnal variation of water uptake and storage ﬂow from the diurnal course of transpiration used as input. The transpiration model is based upon the Penman–Monteith equation and a Jarvis-type representation of the stomatal resistance (i.e., a minimum stomatal resistance multiplied by the product of independent stress functions). Simultaneous measurements of canopy evaporation by an eddy covariance system and water uptake from the soil by sap ﬂow measurements have allowed one to calibrate and validate the model. The capacitance has been found to be equal to 0.17 mm MPa−1 (with a storage hydraulic resistance of about 2 MPa h mm−1 ), generating a time lag of about 1 h between the transpiration rate and the water uptake from the soil. The hydraulic model correctly represents the experimental data. The transpiration model provides reasonable estimates, but with a signiﬁcant scatter. The combined model simulates the diurnal variation of water uptake, storage ﬂow and transpiration rate directly from environmental variables, but in this latter case, the storage ﬂow is estimated with a rather poor accuracy
Keywords: Capacitance; Holm oak; Hydraulic resistance; Non-steady-state model; stomatal resistance; Transpiration; Water storage; Water uptake

Exchange of atmospheric formic and acetic acids with trees and crop plants under controlled chamber and purified air conditions - Kesselmeier, J; Bode, K; Gerlach, C; Jork, E.-M (Atmospheric Environment, 1998)
We investigated the exchange of formic and acetic acids between the atmosphere and various tree species such as beech (Fagus sylvatica L.), ash (Fraxinus excelsior L.), spruce (Picea abies L.) Karst, holm oak (Quercus ilex L.), and birch (Betula pendula L.). and some crop-plant species such as corn (Zea mays, var. Banjo), pea (Pisum sativum, var. Solara), barley (Hordeum vulgare, var. Igri) and oat (Avena sativa, var. Wiesel). All experiments were done with dynamic enclosures ßushed with puriÞed oxidant-free air, containing only low or controlled amounts of the two acids. SigniÞcant and light-triggered emission of both acids from all tree species was observed. For one tree species (ash) a seasonal large increase in fall due to early leaf decomposition was found. The standard emission factors (30¡C and PAR"1000 kmol m2 s~1) given as (nmol m~2 min~1) for acetic and formic acids, respectively, were 8.1 and 29.7 (ash, autumn), 1.0 and 3.3 (ash, summer), 0.9 and 1.4 (beech), 0.7 and 1.45 (spruce), 1.9 and 2.4 (Holm oak) and 1.7 and 6.7 (birch). Rough estimation of global annual emissions range between 20 and 130 Gmol formic acid and 10 and 33 Gmol acetic acid. These numbers reßect a 15Ð30% contribution by forest emissions to the continental organic acid budget. As compared to the global total NMHC emissions low molecular weight organic acids are of minor importance. In contrast to the trees, none of the crop-plant species investigated showed an emission, but always a clear deposition of both acids. Both emission from trees as well as uptake by the agricultural plants could be related to transpiration rates and leaf conductances
Keywords: acetic acid; assimilation; Atmosphere; crop plants; exchange of volatile organic compounds; formic acid; leaf conductance; organic acids; Plants; Transpiration; Trees

Gas exchange measurements and an indirect estimate of primary production in a holm-oak ecosystem - Manes, F; Vitale, M; Feoli, E; Scimone, M; Canfora, E (FRESENIUS ENVIRONMENTAL BULLETIN, 1998)
An original and simple primary production model is presented. Annual trends of the daily average values of net photosynthesis and leaf transpiration for helm oak are showed. Moreover, primary production data were obtained. To validate the model, an evaluation between estimated results and field measurements was performed, obtaining a strong correspondence.
Citation
Keywords: holm-oak; photosynthesis; plant simulation model; primary production; Transpiration

O3 AND 03+C02 EFFECTS ON A MEDITERRANEAN EVERGREEN BROADLEAF TREE, HOLM OAK (QUERCUS iLEX L.) - Manes, F; Vitale, M; Donato, E; Paoletti, E (Chemosphere, 1998)
The aim of this work is to analyze the effects of a) short-term treatments with different concentrations of 0, (daily 6-hour fumigation with 0, 65, 175 and 300 ppb for 3-4 days); and 6) a medium term treatment with O9 (150 ppb three times a week for thirty days on the whole) and CO2 (700 ppm) on gas exchange, chlorophyll fluorescence, and peroxidase activity in holm oak (Quercus ilex L.) leaves. The results show that net photosynthesis, transpiration, Fv/Frvr ratio and POD activity were not influenced until an O1 concentration of 300 ppb was reached. At this threshold, significant alterations in these physiological and biochemical parameters were found. The treatment with +C02 +O, showed an increase of net photosynthesis suggesting thus an antagonistic effect of CO2 with regard to Oj-induced injuries, while CO2 alone increased photosynthesis and decreased transpiration but induced no effects on FV/‘F, ratio or peroxidase activity. From our data, holm oak shows a resistance to episodes ofphotochemical 0, stress, that in the Mediterranean region can reach peaks of > 100 ppb. This response is likely to be due to the morpho-anatomic structure of helm oak leaves and their sclerophyllous adaptations. This might leads helm oak to adopt a stress tolerance strategy with regard to leaf response to O,, the effects of which cannot be ameliorated by an increase of atmospheric CO2
Keywords: CO2 (voyant); Holm oak; Net photosynthesis; ozone exposure; peroxidase activity; Transpiration

Ecophysiological studies of Mediterranean plant species at the Castelporziano estate - Manes, Fausto; Seufert, Günther; Vitale, Marcello (Atmospheric Environment, 1997)
e aim of this work was to characterize the eco-physiological performance of the main plant species of the Castelporziano site by single leaf investigations. We measured the leaf gas exchange of Quercus ilex L., Pinus pinea L., Pistacia lentiscus L. and Asphodelus microcarpus L. for several days. Additionally, the xylem water potential of Quercus ibex, Pinus pinea and Pistacia lentiscus was recorded in order to obtain more physiological background information for the discussion of the trace gas emissions. This study indicates significantly different physiological responses to the different environmental condi- tions. In particular, summer conditions (high values of light, air temperature and low xylem water potentials) caused the depression of photosynthesis in Quercus ibex and Pinus pinea but did not affect photosynthesis of Pistacia lentiscus and Asphodelus microcarpus. This should be taken into account when discussing VOC emission rates and fluxes
Keywords: fluorescence; Phenology; photosynthesis; Transpiration; VOCs; Xylem water potential

Modelling transpiration in holm-oak savannah: scaling up from the leaf to the tree scale - Infante, J M; Rambal, S; Joffre, R (Agricultural and Forest Meteorology, 1997)
The transpiration of oak-savannas in southern Spain was modelled by scaling-up from the leaf to the tree during a drought period. Two chlaracteristics of this ecosystem were found to facilitate the modelling procedure. The first was a near-zero decoupling coefficient between the surface and the surrounding bulk air, which simplifies the transpiration formulation. The second was that the surface conductance (g) is mainly related to the vapour pressure deficit of the air (0,). Based on both of these characteristics, the modelling procedure provides a general model of transpiration over the time scale appropriate for a drought period, from days to months. The response of g to 0, was found to follow a negative exponential function, such that beyo’nd a minimum value, g becomes independent of 0,. This implies a feedback control on g by 0,. The consequences of tbis control for transpiration were found at different levels of plant water status. This explains the plants’ adaptation to long dry periods, even though there is also continuous water loss during these periods. Such an adaptation was corroborated by a seasonal hysteresis found in the relationship between transpiration and D, as a function of the plants’ water status
Keywords: oak savannas; seasonal hysteresis; southern Spain; Transpiration; vapour pressure deficit

Effects of bark-stripping on the water relations of Quercus suber L - Correia, O A; Oliveira, G; Martins-Loução, M a; Catarino, F M (Scientia gerundensis, 1992)
Quercus suber is the primary source of industrial cork and can produce cork every 9-10 years. The main objective of this work was to investigate the influence of bark stripping on the stomatal activity and water relations of cork-oak. For this purpose, diurnal changes on transpiration, stomatal conductance and water potencial were measured before and after bark stripping during July and August 1989 and 1990. The stripping on the trees had been done at various intensities. The water loss by the stripped surface was also measured. These results show that severe bark-stripping may lead to a decrease in stomatal conductance and considerable water losses. The stripping stress is not clearly dependent on the stripping coefficients, but rather on the water lost by the trunk which varies from tree to tree probably according to the phloemic tissues composition.
Keywords: bark-stripping; Quercus suber; Transpiration; water relations

Effects of bark-stripping on the water relations of Quercus suber L - Correia, O. A.; Oliveira, G.; Martins-Loução, M. A.; Catarino, F. M. (Scientia gerundensis, 1992)
Quercus suber is the primary source of industrial cork and can produce cork every 9-10 years. The main objective of this work was to investigate the influence of bark stripping on the stomatal activity and water relations of cork-oak. For this purpose, diurnal changes on transpiration, stomatal conductance and water potencial were measured before and after bark stripping during July and August 1989 and 1990. The stripping on the trees had been done at various intensities. The water loss by the stripped surface was also measured. These results show that severe bark-stripping may lead to a decrease in stomatal conductance and considerable water losses. The stripping stress is not clearly dependent on the stripping coefficients, but rather on the water lost by the trunk which varies from tree to tree probably according to the phloemic tissues composition.
Keywords: bark-stripping; Quercus suber; Transpiration; water relations

Water relations of crok-oak (Quercus suber L.) under natural conditions - Oliveira, G; Correia, O A (Plant Ecology, 1992)
Daily and annual courses of leaf transpiration, stomatal conductance and shoot water potential of four Quercus suber individuals were compared in a semi-natural stand in southwest Portugal, from spring 1989 to early summer 1990. The trees investigated showed annual patterns typical of evergreen sclerophyllous species but varied in their range of stomatal operation. This appeared to be related to differences in hydraulic conductiv- ity in the root-to-leaf pathway. Maximum stomatal conductance and transpiration rates occurred from March to June. Water stress was found to be moderate and winter cold stress due to low air and soil temperatures appeared to have an influence on plant water balance through their effects on flow resistances. Abbreviations." g ..... stomatal conductance; g ....... maximum stomatal conductance, PAR, photosyntheti- cally active radiation; RH, relative humidity of the air; T, leaf transpiration; Ta, air temperature; TL, leaf temperature; T ........ maximum leaf transpiration; AW, air-to-leaf vapor pressure difference; W, shoot water potential; tIJPD, predawn shoot water potential; ttJMIN, minimum shoot water potential.
Keywords: Mediterranean climate; montado; Quercus suber; soil-to-leaf hydraulic conductivity; Stomatal conductance; Transpiration

Water relations of crok-oak (Quercus suber L.) under natural conditions - Oliveira, G; Correia, O A (Plant Ecology, 1992)
Daily and annual courses of leaf transpiration, stomatal conductance and shoot water potential of four Quercus suber individuals were compared in a semi-natural stand in southwest Portugal, from spring 1989 to early summer 1990. The trees investigated showed annual patterns typical of evergreen sclerophyllous species but varied in their range of stomatal operation. This appeared to be related to differences in hydraulic conductiv- ity in the root-to-leaf pathway. Maximum stomatal conductance and transpiration rates occurred from March to June. Water stress was found to be moderate and winter cold stress due to low air and soil temperatures appeared to have an influence on plant water balance through their effects on flow resistances. Abbreviations." g ..... stomatal conductance; g ....... maximum stomatal conductance, PAR, photosyntheti- cally active radiation; RH, relative humidity of the air; T, leaf transpiration; Ta, air temperature; TL, leaf temperature; T ........ maximum leaf transpiration; AW, air-to-leaf vapor pressure difference; W, shoot water potential; tIJPD, predawn shoot water potential; ttJMIN, minimum shoot water potential.
Keywords: Mediterranean climate; montado; Quercus suber; soil-to-leaf hydraulic conductivity; Stomatal conductance; Transpiration

Effects of temperature at constant air dew point on leaf carboxylation efficiency and CO 2 compensation point of different leaf types - Weber, J. A.; Tenhunen, J. D.; Lange, O. L. (Planta, 1985)
The effect of temperature on photosyn- thesis at constant water-vapor pressure in the air was investigated using two sclerophyll species, Ar- butus unedo and Quercus suber, and one meso- phytic species, Spinacia oleracea. Photosynthesis and transpiration were measured over a range of temperatures, 20-39 ~ C. The external concentra- tion of CO 2 was varied from 340 ~tbar to near CO 2 compensation. The initial slope (carboxylation effi- ciency, CE) of the photosynthetic response to inter- cellular CO 2 concentration, the CO 2 compensation point (/-), and the extrapolated rate of CO 2 re- leased into COa-free air (Ri) were calculated. At an external CO 2 concentration of 320-340 labar CO2, photosynthesis decreased with temperature in all species. The effect of temperature on F was similar in all species. While CE in S. oleracea changed little with temperature, CE decreased by 50% in Q. suber as temperature increased from 25 to 34 ~ C. Arbutus unedo also exhibited a de- crease in CE at higher temperatures but not as marked as Q. suber. The absolute value of Ri in- creased with temperature in S. oleracea, while changing little or decreasing in the sclerophylls. Variations in F and Ri of the sclerophyll species are not consistent with greater increase of respira- tion with temperature in the light in these species compared with S. oleracea.
Keywords: Carboxylation efficiency; Compensation point (CO2); Photosynthesis (temperature-humidity); Sclerophyll; Transpiration